56 Quality Improvement Project on the Bowel Charts in An Elderly Care Ward in Basildon University Hospital. (6th February 2020) - Hakim, R A; Ali, M; Wijenyake, I
Abstract: Background: To improve the rate of documentation on bowel charts on an elderly care ward with a significant percentage of patients suffering from dementia. Importance: As a junior doctor working on an elderly care ward with patients who often had memory problems and were unable to recall their bowel patterns, it was extremely challenging to establish whether a particular patient has constipation or diarrhoea. Constipation in an elderly patient can lead to multiple complications like urinary retention, intestinal obstruction and often decreased oral intake. Methods: An audit was carried out to see the rate of completion of the Bowel charts on the ward. Only about 23% of the bowel charts on the ward were complete in the initial survey. Then interventions were introduced in steps and three more audits were done. At each step, we were able to show how the interventions introduced changed the degree of completion of the bowel charts. Outcome: We have seen a marked improvement of 37% since the start of the project 5 months ago. From 23% to 60% completion of bowel charts. There appeared to be a sustained change only falling short at the weekends (due to staffing issues) Overall awareness had increased vastly. We were able to make a measurable change and improvement in the quality of care provided.